Neurological assessment and immediate outcome of newborns treated with therapeutic hypothermia at tertiary care hospital of southern Rajasthan-a randomized control trial - Goyal, Suresh; Sanadhya, Anuradha; Mehrotra, Juhi; Jain, Bhupesh; Kachhwaha, Ritika (International Journal of Contemporary Pediatrics, 2021)
Background: Therapeutic hypothermia (TH) is standard-of-care for infants with moderate and severe HIE in developed countries; TH has been shown to decrease the risk of brain injury in asphyxiated newborns. Observations were like: 1) Asses morbidity and mortality in neonates with moderate and severe birth asphyxia treated with TH and 2) Asses neurological outcome in neonates. Methods: A RCT was done in NICU of Balchikitsalaya, RNTMC, Udaipur. Phase changing material, FS 21, FS 29 used to provide TH for 72 hours, started within 6 hours of birth and neurological outcome was assessed. Results: Total 60 neonates were enrolled 30 cases given TH and 30 control not given TH. Neurological assessment on basis of Thompson scoring, done on admission, 24, 48, 72 and 96 hours for both groups. At 48 hours, mean score in controls 14.5±1.67 and cases 11.47±2.34 (p<0.05). At discharge, mean score for controls was 11.31±3.67 and for cases was 5.24±2.72 (p<0.005). Mortality was 4 (13.3%) in cases and 11 (36.7%) in control group. Among 45 survivors, 25 (55.5%) required anticonvulsant at discharge; 15 from controls, 10 from cases group. Conclusions: There was significant decrease in mortality in birth asphyxia babies given TH as compared to babies not given TH. Also, significant improvement in Thompson score among the cooled neonates at and after 48 hours of age suggestive of better immediate neurological outcome in these babies. Anticonvulsant’s requirement was also significantly less in therapeutic hypothermia group.